Editorial: A Reflective Take on The Government Decisions in Facing Global Uncertainty - Shadu Satwika Wijaya (JUSS (Jurnal Sosial Soedirman), 2023)
Editorial: Refleksi Keputusan Pemerintah dalam Menghadapi Ketidakpastian Global